John of the Woods - Brown, Abbie Farwell, 1871-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"John of the Woods" by Abbie Farwell Brown is a children's fantasy novel written in the early 20th century. The story introduces us to a young boy named Gigi, a tumbler who has escaped from the cruel treatment of his Gypsy masters. The narrative unfolds in a whimsical setting where Gigi's adventures lead him into the depths of a forest, ultimately transforming his life as he aligns himself with the kind-hearted hermit and a variety of animals that populate his new world. At the start of the novel, readers are introduced to Gigi's life within a traveling troupe of tumblers, where he is oppressed and beaten by his masters. During a performance, he is deeply unhappy and dreams of escape. Following a near-fatal incident during the act, Gigi is given a glimmer of hope by a compassionate woman from the audience who encourages him to run away. Seizing the opportunity when his captors venture to the inn, he decides to flee, finding brief solace in a kind family before venturing into the woods. Gigi soon encounters an old hermit who becomes a father figure, allowing him to embrace a more compassionate and peaceful existence away from the cruelty he has suffered. The beginning of Gigi's journey serves as a poignant reflection of resilience, transformation, and the warmth of newfound freedom. (This is an automatically generated summary.)
Release date is 2004-10-31
Produced by Al Haines
Keywords: Runaway children -- Juvenile fiction; Hunters -- Juvenile fiction; Forest animals -- Juvenile fiction